A Narrative Review: Serotonin Reuptake Inhibitors and the Risk of Suicidal Ideation in Adolescents - Dylan S. Gage; Veronica E. Priefer; Ronny Priefer (Adolescents)
Abstract: Serotonin reuptake inhibitors (SSRIs) are currently the first-line treatment for adolescents suffering from major depressive disorder, even though a black box warning concerns suicidal ideation was put forth in 2004. Numerous trials have been conducted evaluating this risk in adult patients, with less being done surrounding pediatric patients. Trials that have focused on this specific risk in adolescents have shown either a strong connection, conflicting results, or non-significance. Trials comparing other non-SSRI antidepressants have also demonstrated some risk of suicidal ideation, suggesting the risk may not be specific to this class of drugs. Other data have also suggested that the risk is linked to treatment duration, genetics, and/or simply that the adolescent patients with major depressive disorder are an at-risk population. Herein, a review is presented of the trials conducted surrounding SSRIs, their use in adolescents, and their risk in terms of developing suicidal ideation.